2012
DOI: 10.1159/000336226
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Congenital Pulmonary Airway Malformation Induced Hydrops Fetalis via Percutaneous Sclerotherapy

Abstract: Large type II and III congenital pulmonary airway malformations (CPAMs) can cause pulmonary hypoplasia, non-immune hydrops fetalis and fetal demise. Fetal intervention is indicated if hydrops fetalis develops. In this report, we describe three cases of type II and III CPAMs complicated by hydrops and treated with percutaneous sclerotherapy by ethanolamine injection into the tumor. All 3 cases demonstrated reduction in size of the CPAM and resolution of the hydrops with subsequent delivery at term. We believe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
0
14
0
2
Order By: Relevance
“…Intrauterine sclerotherapy has been used to treat fetal pleural effusion, cystic hygroma, and bronchopulmonary sequestration [18,19,20]. Recent reports also demonstrated that complicated CCAM can be managed by fetal sclerotherapy and they concluded this treatment modality is minimally invasive and highly effective [21,22]. OK-432, which is widely used as a safe and effective sclerosing agent, can break down the normal epithelia of cystic walls via inflammatory reactions and the resulting fibrotic adhesions cause lymphatic fluid reduction and shrinkage [23].…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine sclerotherapy has been used to treat fetal pleural effusion, cystic hygroma, and bronchopulmonary sequestration [18,19,20]. Recent reports also demonstrated that complicated CCAM can be managed by fetal sclerotherapy and they concluded this treatment modality is minimally invasive and highly effective [21,22]. OK-432, which is widely used as a safe and effective sclerosing agent, can break down the normal epithelia of cystic walls via inflammatory reactions and the resulting fibrotic adhesions cause lymphatic fluid reduction and shrinkage [23].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding minimally invasive fetal surgery, percutaneous laser ablation of the lung mass has been attempted with disappointing results [14]. In 2 previous reports, during percutaneous sclerotherapy ethanolamine or polidocanol was injected into the lung mass of 6 fetuses with CCAM and hydrops, including 2 cases with solid microcystic CCAM (type III) [15,16]. The authors reported progressive reduction in the size of the lung mass in all but one case, and resolution of the hydrops and delivery at term in all cases with an overall survival rate of 83% (5/6).…”
Section: Discussionmentioning
confidence: 99%
“…The administration of maternal betamethasone is not offered as a primary treatment for CPAM type II or III at our center, but is taken into consideration on a case‐by‐case basis. After informed consent was obtained, patients who elected sclerotherapy underwent ultrasound‐guided percutaneous sclerotherapy using 5% ethanolamine oleate (EO), as previously described . In brief, a 22‐gauge needle (in one case, we used a 19‐gauge) was inserted into an avascular portion of the fetal chest mass, and 2‐mL aliquots of EO were injected.…”
Section: Methodsmentioning
confidence: 99%
“…For select cases of CPAM type II or III complicated by hydrops, lobectomy by open fetal resection has been offered as a salvage therapy at a few fetal surgery centers in the United States. Given the maternal morbidity associated with open fetal surgery, less invasive alternatives have been explored including interstitial laser ablation and percutaneous sclerotherapy of the chest mass . To date, there are 6 reported cases of CPAM II or III treated in utero with sclerotherapy; 3 of these are again included in this case series.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation